Tool wear and wear mechanism of WC-Co End Mill during milling of CFRP in sustainable cutting conditions - Abd Halim, Nor Farah Huda; Mustafa, Aisyah Madihah; Shaharudin, N.S.; Dahnel, Aishah Najiah; Tomadi, Siti Haryani; Ahmad, Zuraida; Adesta, E.Y.T.; Rahman, M. (Trans Tech Publications Ltd, 2023)
Carbon Fiber-Reinforced Polymer (CFRP) has been in great demand in the aerospace and automotive industries due to its exceptional strength-to-weight ratio. Machining CFRP is a challenge as dry machining results in high cutting temperature especially with high cutting speeds that compromise the glass transition temperature (Tg) and degrades the matrix resin epoxy. A sustainable cutting environment such as chilled air is utilized as an alternative cutting media in reducing the heat generated during machining process to reduce the tool wear and improved the surface quality of the CFRP. Therefore, this research is conducted to study the progression of uncoated tungsten carbide (WC-Co) tool wear when milling CFRP in a three different cutting conditions which are dry, coolant and chilled air with a constant cutting parameter. The CFRP was milled with a constant speed of 170 m/min, feed rate of 2100 mm/min and 1 mm depth of cut for a total of 6000 mm machining length. It was found that milling in chilled air resulted in the highest flank wear of 0.110 mm, which is higher compared with dry and coolant cutting condition. This is contributed by the additional abrasion of CFRP dust-like chips on the cutting edge of the carbide tool. The presence of the chilled air during milling of CFRP aided in maintaining the surface hardness thus resulted in increasing of tool wear as compared with dry and coolant cutting conditions